Desempenho agronômico de cultivares de rúcula em cultivo de primavera e inverno sob sombreamento - Abade, Mayra Taniely Ribeiro (2018)
The objective of this work was to evaluate the morphometry, growth, physiology and chemical composition of two arugula cultivars in four growing environments (full sun, 30%, 50% and 70% shading) in spring and winter and in protected environment in the spring . The experiments in culture environment were conducted in randomized blocks with four replicates, while the one conducted in a protected environment had eight blocks. In the spring and summer shades were tested, in the cultivars of Arugula Folha Larga and Cultivada. In the spring in a greenhouse, three cultivars of arugula (Folha Larga, Cultivada and Donatella) were tested. The parameters analyzed in all the experiments were: leaf area; number of leaves; diameter of the collection and mass of dry matter, was also performed growth analysis and determination of photosynthetic pigments, and quality analysis in the winter experiment. The results of article I demonstrate that the use of shading in arugula culture is only beneficial to some extent, abrupt reductions in solar radiation negatively affect plant morphology, physiology and biochemistry. In the second article it was obtained that the cultivars of Arugula Folha Larga and Cultivada are agronomically more efficient than the cv. Donatella, under the conditions studied, because they present better quantitative and qualitative performance, besides better morphophysiological indexes, when cultivated in a protected environment. At certain periods the air temperature was higher than the crop limit, however, there were no damages to the plant growth and production. In the third article, the arugula morphometry was influenced by the amount of radiation to which the plant is exposed; plants grown in more shaded environments (70%) had lower values of leaf area, leaf number, collection diameter, mass of dry matter and height. Plants submitted to higher light regimes reached higher absolute growth rate, relative growth rate, net assimilation rate and relative growth rate of leaf area, when compared to plants submitted to lower light intensities, which presented higher leaf area ratio. Environmental factors such as light, temperature significantly affect the net assimilation rate, relative growth rate, absolute growth rate, of these plants. Regarding production, the results obtained for full sun, 30% and 50% did not differ statistically from each other and were satisfactory, while 70% shading resulted in lower production averages. For the quality of arugula plants demonstrated in the fourth article, it was observed that it is directly influenced by environmental conditions and also varies depending on the cultivar used. For arugula cultivation in winter, the environment that provided plants with the best chemical quality results was 30% shading.